PENGARUH SUDUT SERANG TERHADAP KINERJA TURBIN ANGIN HELIKS GORLOV DENGAN PENAMBAHAN CURVEPLATE - Fadhil, Muhammad (Universitas Negeri Semarang, 2020)
Abstract. Ã‚Â At present, source of energy is used from fossil fuels. To overcome the fossil fuels that cause pollution effects to the environment, needs a development on renewable energy. The development can be channeled through a wind turbine. To improve the performance of GorlovÃ¢â‚¬â„¢s helical turbine there are several factors that influence, one of them is the angle of attack. The innovation can be do is change the angle of attack to 90Ã‚Â° and adding curveplate, this innovation can provide greater power yield and power coefficient compared to the GorlovÃ¢â‚¬â„¢s helical turbine that already currently used. This is because change the angle of attack conduce lift and drag force on blade are change.Ã‚Â With the right angle of attack can provide more positive forces that help the turbine rotating. The more force that help the turbine rotating made the more power generated.